Automation, Production Systems, and Computer-Integrated Manufacturing, Global Edition - Groover, Mikell P.; Groover, Mikell (Pearson International Content, 2015)
Automation, Production Systems, and Computer-Integrated Manufacturing is appropriate for advanced undergraduate/ graduate-level courses in Automation, Production Systems, and Computer-Integrated Manufacturing. This exploration of the technical and engineering aspects of automated production systems provides the most advanced, comprehensive, and balanced coverage of the subject of any text on the market. It covers all the major cutting-edge technologies of production automation and material handling, and how these technologies are used to construct modern manufacturing systems. This book will provide a better teaching and learning experience—for you and your students. It will help: Provide Balanced Coverage of Automated Production Systems: A quantitative approach provides numerous equations and example problems for instructors who want to include analytical and quantitative material in their courses. Support Learning: End-of-chapter problems, review questions, and problem exercises give students plenty of opportunities to put theory into action. Keep Your Course Current: This edition provides up-to-date coverage of production systems, how they are sometimes automated and computerised, and how they can be mathematically analysed to obtain performance metrics. The full text downloaded to your computer With eBooks you can: search for key concepts, words and phrases make highlights and notes as you study share your notes with friends eBooks are downloaded to your computer and accessible either offline through the Bookshelf (available as a free download), available online and also via the iPad and Android apps. Upon purchase, you'll gain instant access to this eBook. Time limit The eBooks products do not have an expiry date. You will continue to access your digital ebook products whilst you have your Bookshelf installed.